Adipokines and cardiovascular disease: A comprehensive review - Smekal, Ales; Vaclavik, Jan (Biomedical papers, 2017)
Adipokines are peptides that signal the functional status of adipose tissue to the brain and other target organs. In adipose tissue dysfunction, adipokine secretion is altered, and this can contribute to a spectrum of obesity-associated conditions including cardiovascular disease. Some adipokines have anti-inflammatory and cardioprotective effects (omentin, apelin, adiponectin). Others are pro-inflammatory with negative impact on cardiovascular function (leptin, visfatin, resistin, adipocyte fatty-acid-binding protein). In the first part, this article reviews the endocrine functions of adipose tissue in general, effects of the distribution and composition of fat tissue, and the roles of cortisol and the renin-angiotensin-aldosterone system in the development of the inflammatory state of addipose tissue. In the second part, the known cardiovascular effects of different adipokines and their clinical potential are discussed in detail.
Keywords: adipokines; obesity; adipose tissue; cardiovascular effects; myocardial infarction; heart failure; omentin; apelin; adiponectin; leptin; visfatin; resistin; adipocyte fatty-acid-binding protein